Comprehensive Analysis of Metabolic Changes in Mice Exposed to Corilagin Based on GC-MS Analysis - Xu B; Wang C; Zhu X; Zhu L; Han G; Cui C (Drug Design, Development and Therapy)
Biao Xu,1,* Changshui Wang,2,* Xiaodong Zhu,2 Li Zhu,3 Guangkui Han,2 Changmeng Cui2 1Clinical Medical School, Jining Medical University, Jining, 272067, People’s Republic of China; 2Department of Neurosurgery, Affiliated Hospital of Jining Medical University, Jining Medical University, Jining, 272000, People’s Republic of China; 3Translational Pharmaceutical Laboratory, Jining No. 1 People’s Hospital, Shandong First Medical University, Jining, 272000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Changmeng Cui; Guangkui Han, Department of Neurosurgery, Affiliated Hospital of Jining Medical University, 89 Guhuai Road, Jining, Shandong, 272000, People’s Republic of China, Tel +86 0537 2908518, Email cmcuidr1989@163.com; guangkui_han@163.comBackground: Corilagin is widely distributed in various medicinal plants. In recent years, numerous pharmacological activities of Corilagin have been reported, including anti-inflammatory, antiviral, hepatoprotective, anti-tumor, and anti-fibrosis effects. However, there is still a need for systematic metabolomics analysis to further elucidate its mechanisms of action. The aim of this study was to explore the pharmacological mechanism of Corilagin.Methods: This study utilized gas chromatography-mass spectrometry (GC-MS) to analyze central target tissues, comprehensively exploring the pharmacological mechanism of Corilagin in mouse models. We identified the differential metabolites by multivariate analyses, which include principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA). Using MetaboAnalyst 5.0 and the KEGG database was used to depict the 12 key metabolic pathways.Results: Compared with the control group, the Corilagin induced 20, 9, 11, 7, 16, 19, 14, 15, and 16 differential metabolites in the intestine, lung, kidney, stomach, heart, liver, hippocampus, cerebral cortex, and serum, respectively. And 12 key pathways involving glucose metabolism, lipid metabolism, and amino acid metabolism were identified following Corilagin treatment.Conclusion: This research provides insight into the action mechanism of Corilagin’s anti-oxidative, anti-inflammatory, anti-atherosclerotic, hepatoprotective, anti-tumor, and neuroprotective properties. Keywords: Corilagin, gas chromatography-mass spectrometry, metabolomics, amino acids, pharmacological mechanism